KONSELING MODEL RASIONAL EMOTIF DALAM MENANGGULANGI GANGGUAN EMOSIONAL SISWA - Putu Agus Semara Putra Giri (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
Emotional rational counseling is carried out using varied and systematic procedures that are specifically intended to change behavior within the boundaries of goals compiled jointly by the counselor and client. The counselor's duties show that the problem is caused by disturbed perceptions and thoughts that are distracted. irrational and the attempt to solve the problem is to return to the original causes. The operationalization of the counselor's duties: (a) More educative-directive to clients, by providing lots of stories and explanations, especially at the initial stage of confronting client problems directly, (b) Using approaches that can encourage and improve the client's thinking, then improve they are able to educate themselves persistently and repeatedly emphasize that irrational ideas are what cause emotional barriers to clients, (c) encourage clients to use rational abilities rather than emotions, and (d) Use educational and philosophical approaches using humor and “suppressing